Chemotherapy versus chemoradiotherapy in borderline resectable and locally advanced pancreatic adenocarcinoma - Argalácsová, Soňa; Vočka, Michal; Petruželka, Luboš; Ryska, Miroslav; Záruba, Pavel; Krška, Zdeněk; Frýba, Vladimír; Ulrych, Jan; Černý, Vladimír; Tůma, Tomáš; Hoskovec, David (Neoplasma, 2023)
The role of radiotherapy in borderline resectable (BRPC) and locally advanced pancreatic carcinoma (LAPC) remains controversial. In our study, we retrospectively evaluated 48 patients with BRPC (14; 29.2%) and LAPC (34; 70. 8%) who underwent 6-8 cycles of induction mFOLFIRINOX chemotherapy alone (23; 47.9%) or 4-6 cycles of mFOLFIRINOX followed by hypofractionated radiotherapy (up to the total dose of 39.9 Gy in 15 fractions) (25; 52.1%). Survival parameters were evaluated using the Gehan-Breslow-Wilcoxon Test and compared by using the long-rank test. The addition of radiotherapy was not associated with better survival (16.9 months for chemotherapy only versus 15.9 months for the combined therapy; p=0.486), as well as for both subgroups (13.5 months vs. 18.3 months; p=0.679) and (20.7 months vs. 13.8 months; p=0.425) for BRPC and LAPC, respectively. A higher resection rate was seen in the BRPC group compared to the LAPC group (43% vs. 17.6%, respectively). Our study revealed a significantly higher rate of lung metastases in patients after the combination therapy compared to those treated by chemotherapy only (19% vs. 0%, respectively; p=0.045). Such a borderline result, however, prevents us from drawing clear conclusions about whether this is an artifact caused by the low number of patients or whether radiotherapy leads to a selection of stem cells with a predilection to the generalization to the lungs.
Keywords: chemoradioterapie; protokoly protinádorové kombinované chemoterapie; Pancreatic Neoplasms; Humans; Neoadjuvant Therapy; retrospektivní studie; lidé; Adenocarcinoma; nádory slinivky břišní; Retrospective Studies; adenokarcinom; Chemoradiotherapy; Antineoplastic Combined Chemotherapy Protocols; neoadjuvantní terapie